The Implementation of Wavepad Application to Improve Listening Students - Gustiara Sari, Dini; Lee, Chuen; Xamper, Xamper (Journal International of Lingua and Technology, 2022)
This article describes the important role of learning media with its influence on students' special maharah skills. Learning media is very necessary in this technological era. So educators must be able to keep up with technological developments. Educators are expected to be proficient in keeping up with technological developments. In improving the Arabic language, students are also supported by technology. It can be said that researchers in this case utilize wavepad audio learning media to increase students' special gifts. In this study, researchers used qualitative analysis methods. The method used by this researcher describes how to increase students' special gifts through wavepad learning media. Learning with wavepad media aims to convey the message content of a material, stimulate the sharpness of students' understanding and strengthen the vocabulary mastered by students. And through this learning role, educators can guide students to master the mahrah istima' material properly and correctly.